Comparison of the effects of land-based and grass-based plyometric training on leg power, muscle activity and muscle soreness among active young males - Meng, Ng Jun (2018)
The purpose of this study was to compare the effects of land-based and grass-based plyometric on leg power, muscle activity and muscle soreness among active young males. Eighteen young males were recruited and they were divided into two groups, i.e. land-based (Age:21.3±1.6 years old; body height: 172.6±3.7cm; body weight: 65.8±7.4kg; BMI: 22.1±2.4kg.m-2; body fat percentage:16.6±3.2%) and grass-based (Age: 20.6±1.9 years old; body height: 169.8±2.3cm; body weight: 64.4±8.4kg; BMI: 22.3±2.9kg.m-2; body fat percentage: 17.4±2.6%) plyometric training groups. Participants in both groups underwent 6 weeks (3 sessions per week) of same plyometric training programme. Performance outcome variables were peak power (vertical jump), average power (isokinetic testing at the angular velocities of 1800.s-1 and 3000.s-1), EMG activity (vastus lateralis, vastus medialis, rectus femoris and lateral gastrocnemius). Muscle soreness of the lower limb was determined by using Visual Analogue Scale (VAS). Paired t-test was used to analyse all the parameters except for scale of muscle soreness where repeated measures ANOVA was used. Vertical jump height was significantly higher (p<0.05) at pre-test compared to its p-test value in land-based training group. However, there was also trend of improvement in this parameter in grass-based group. There were significantly higher values of knee extension average power at 1800.s-1 and 3000.s- 1 in post-test compared to pre-test values for non-dominant leg in grass-based plyometric group. In land-based plyometric group, there were significantly higher values of knee extension average power at 1800.s-1 for dominant leg, 3000.s-1 for dominant and non-dominant legs, and knee flexion average power at 1800.s-1 for non-dominant leg. Both grass- and land-based groups exhibited significantly higher EMG activity of vastus medialis for non-dominant leg in posttest compared to pre-test. Degree of muscle soreness was significantly lower at second, fifth and sixth week in grass-based training group compared to land-based training group. In conclusion, land-based plyometric training provided more discernable beneficial training effects on vertical jump height and isokinetic knee extension and flexion average power compared to grass-based training. However, grass-based training induced lower muscle soreness. Therefore, grass-based plyometric training may be an alternative for individuals to improve leg power while reducing the degree of muscle soreness.